Tight Regulation of Major Histocompatibility Complex I for the Spatial and Temporal Expression in the Hippocampal Neurons - Shen, Yuqing; Zhang, Jianqiong (Frontiers in Cellular Neuroscience, 2021)
The expression and function of immune molecules, such as major histocompatibility complex (MHC), within the developing and adult brain have been discovered over the past few years. Studies utilizing classical class Ⅰ MHC knockout animals suggest that these molecules are in fact playing essential roles in the establishment, function and modification of synapses in the CNS. Altered neuronal expression of class Ⅰ MHC, as has been reported in pathological conditions, leads to aberrations in neuronal development and repair. In the hippocampus, cellular and molecular mechanisms that regulate synaptic plasticity have heretofore been extensively studied. It is for this reason that multiple studies directed at better understanding the expression, regulation and function of class Ⅰ MHC within the hippocampus have been undertaken. Since several previous reviews have addressed the roles of class Ⅰ MHC in the formation and function of hippocampal connections, the present review will focus on describing the spatial and temporal expression of class Ⅰ MHC in developing, healthy adult and aging hippocampus. Herein we also review current literature exploring mechanisms which regulate class Ⅰ MHC expression in murine hippocampus. With this review we aim to facilitate a deeper mechanistic understanding into the complex tight regulation of MHC Ⅰ expression in hippocampus, which are needed as we explore the potential for targeting MHC Ⅰ for therapeutic intervention in normal aging and in neurodegenerative diseases in the future.